Enrichment Book Development on Writing Descriptive Texts with a Communication Skills Orientation with Unity Character Values - Nurul Fitrotul Aimatul Khoiri; Subyantoro Subyantoro; Haryadi Haryadi (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
Enrichment books are companion books to textbooks used in school learning. Current enrichment books on writing descriptive texts mostly focus solely on knowledge aspects. However, those that focus on skill development often lack completeness and optimization in the material presented. Therefore, there is a need for the development of enrichment books to deepen the content of writing descriptive texts oriented towards communication skills and values of national unity character for 7th-grade junior high school students. The research design employed in this study is the Research and Development (R&D) design, utilizing data from the needs of students and educators. The outcome of this research is a prototype of an enrichment book on writing descriptive texts oriented towards communication skills and values of national unity character for 7th-grade junior high school students, comprising (1) book cover, (2) introductory section, (3) main content, and (4) concluding section. The principles of enrichment books used in developing this prototype include completeness, ease of use, communicativeness, attractiveness, coherence, and novelty.